INFLATION PERSISTENCE IN NORTH SUMATERA PROVINCE - Wily Julitawaty (Universitas Negeri Medan, 2014)
The purpose of this study was to determine the persistence of inflation in major North Sumatera Province in 2007 until 2012 and value contributed Output Growth (GDP) of North Sumatera, Exchange Rate, Interest Rate and Error Correction Term about Inflation in North Sumatera. Data is used secondary data from general Consumer Price Index (CPI) from North Sumatera Province include Medan, Pematangsiantar, Sibolga and Padangsidempuan monthly of January 2007 until December 2012. And secondary data Consumer Price Index (CPI) of North Sumatera Province, Gross Domestic Product of Province Sumatera Utara, Exchange Rate and Interest Rate of BI Rate yearly of 1999 until 2012. Model is used model econometric with Autoregressive method and Error Correction Model. Result of this research with estimation of VAR model concludes that degree of persistence of 4 town from North Sumatera Province is low. Result of estimation of model ECM concludes that Interest Rate significantly affect to inflation rate, while Gross Domestic Product of North Sumatera Province and Exchange Rate not significantly affect to inflation rate. While ECT becomes significant correction to variable inflation rate. Where the form of error correction in the ECM suggests a long-term relationship between the variables inflation, GDP variable, the variable exchange rate and variable interest rate is comparable.